CALCULATION OF THE LOAD ON THE FRICTION CLUTCH OF THE SEWING MACHINE - Dustova, Firuza; Babadjanov, Sabit (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article considers a disc friction clutch, a sewing machine drive, the condition for its performance, the calculation of axial force, and the wear resistance of a friction pair. In the process of switching on the friction clutch, sliding occurs between the parts with which the clutch halves are engaged. It is noted that the adhesion strength in the clutch depends on the coefficient of friction and its stability when changing the sliding speed, pressure and temperature.